Denosumab increases sublesional bone mass in osteoporotic individuals with recent spinal cord injury. Issue 1 (January 2016) - Gifre, L.; Vidal, J.; Carrasco, J.; Muxi, A.; Portell, E.; Monegal, A.; Guañabens, N.; Peris, P.
Abstract Summary Osteoporosis is a frequent complication related to spinal cord injury (SCI), and data on osteoporosis treatment after SCI is scarce. Treatment with denosumab increases lumbar and femoral BMD and decreases bone turnover markers in individuals with recent SCI. This drug may be a promising therapeutic option in SCI-related osteoporosis. Introduction Osteoporosis development is a frequent complication related to SCI, especially at the sublesional level. Nevertheless, data on osteoporosis treatment after SCI is scarce, particularly short term after injury, when the highest bone loss is produced. The aim of this study was to analyze the efficacy of denosumab in the treatment of SCI-related osteoporosis. Methods Fourteen individuals aged 39 ± 15 years with osteoporosis secondary to recent SCI (mean injury duration 15 ± 4 months) were treated with denosumab for 12 months. Bone turnover markers (BTMs) (PINP, bone ALP, sCTx), 25-hydroxyvitamin D (25OHD) levels and bone mineral density (BMD) at the lumbar spine (LS), total hip (TH), and femoral neck (FN) were assessed at baseline and at 12 months. All participants received calcium and vitamin D supplementation. Results At 12 months, SCI denosumab-treated participants showed a significant increase in BMD at TH (+2.4 ± 3.6 %, p  = 0.042), FN (+3 ± 3.6 %, p  = 0.006), and LS (+7.8 ± 3.7 %, p  < 0.001) compared to baseline values. Denosumab treatment was associated with significant decreases in BTMs (bone ALP −42 %, p  < 0.001; PINP −58 %, p  < 0.001, sCTx −57 %, p  = 0.002) at 12 months. BMD evolution was not related to BTM changes or 25OHD serum levels. No skeletal fractures or serious adverse events were observed during follow-up. Conclusions Treatment with denosumab increases lumbar and femoral BMD and decreases bone turnover markers in individuals with recent SCI. This drug may be a promising therapeutic option in SCI-related osteoporosis.